Engineering Manhood : Race and the Antebellum Virginia Military Institute - Miller, Jonson (Book collections on Project MUSE., 2020)
It is not an accident that American engineering is so disproportionately male and white; it took and takes work to create and sustain this situation. Engineering Manhood: Race and the Antebellum Virginia Military Institute examines the process by which engineers of the antebellum Virginia Military Institute cultivated whiteness, manhood, and other intersecting identities as essential to an engineering professional identity. VMI opened in 1839 to provide one of the earliest and most thorough engineering educations available in antebellum America. The officers of the school saw engineering work as intimately linked to being a particular type of person, one that excluded women or black men. This particular white manhood they crafted drew upon a growing middle-class culture. These precedents impacted engineering education broadly in this country and we continue to see their legacy today.